Biomarkers to identify ILD and predict lung function decline in scleroderma lung disease or idiopathic pulmonary fibrosis - Kennedy, Barry; Branagan, Peter; Moloney, Fiachra; Haroon, Muhammad; O'Connell, Oisin J; O'Connor, Terence M; O'Regan, Kevin; Harney, Sinead; Henry, Michael T (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
Background: SSc-ILD and IPF demonstrate significant morbidity and mortality. Predicting disease progression is challenging in both diseases. Objectives: We sought a serum biomarker that could identify patients with SSc-ILD or IPF and prospectively predict short-term decline in lung function in these patients. Methods: 10 healthy controls, 5 SSc w/o ILD, 6 SSc-ILD and 13 IPF patients underwent venesection. An array of cytokines including KL-6, SP-D and MMP7 were measured.  PFTs were obtained at baseline and six months. Cytokine measurements were correlated with PFTs. Results: KL-6 in IPF patients (633ng/ml, IQR 492-1675) was significantly elevated compared to controls (198ng/ml, IQR 52-360, p